Cost Accounting: Concepts and Techniques for Management (Book). - Nordhauser, Fred; Hendrickson, Harvey S. (The Accounting Review, 1986)
Reviews the book "Cost Accounting: Concepts and Techniques for Management," by Larry N. Killough and Wayne E. Leininger.